2021
DOI: 10.3389/fcell.2021.732952
|View full text |Cite
|
Sign up to set email alerts
|

ADAM17, A Key Player of Cardiac Inflammation and Fibrosis in Heart Failure Development During Chronic Catecholamine Stress

Abstract: Heart failure development is characterized by persistent inflammation and progressive fibrosis owing to chronic catecholamine stress. In a chronic stress state, elevated catecholamines result in the overstimulation of beta-adrenergic receptors (βARs), specifically β2-AR coupling with Gαi protein. Gαi signaling increases the activation of receptor-stimulated p38 mitogen-activated-protein-kinases (p38 MAPKs) and extracellular signal-regulated kinases (ERKs). Phosphorylation by these kinases is a common way to po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 160 publications
(293 reference statements)
0
18
0
Order By: Relevance
“…Among these DEPs, ADAM17, a metalloprotease, has been indicated to participate in inflammation, fibrosis, and immunity using its proteolytic activity, eventually aggravating cardiac dysfunction. 27 Other study suggested that abnormal ADAM17 expression can cause airway fibrosis in chronic obstructive asthma. 28 ITGB3 is a multifunctional cell surface receptor and regulates downstream intracellular signals including cell adhesion, proliferation, migration, survival, and differentiation.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these DEPs, ADAM17, a metalloprotease, has been indicated to participate in inflammation, fibrosis, and immunity using its proteolytic activity, eventually aggravating cardiac dysfunction. 27 Other study suggested that abnormal ADAM17 expression can cause airway fibrosis in chronic obstructive asthma. 28 ITGB3 is a multifunctional cell surface receptor and regulates downstream intracellular signals including cell adhesion, proliferation, migration, survival, and differentiation.…”
Section: ■ Discussionmentioning
confidence: 99%
“…By analyzing the DEPs between Con EVs and PD EVs, we found that up-regulated proteins in PD EVs were enriched in response to wounding and leukocyte migration, supporting the development of fibrosis. Among these DEPs, ADAM17, a metalloprotease, has been indicated to participate in inflammation, fibrosis, and immunity using its proteolytic activity, eventually aggravating cardiac dysfunction . Other study suggested that abnormal ADAM17 expression can cause airway fibrosis in chronic obstructive asthma .…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in A disintegrin and metalloprotease 17 (ADAM17) can cause VEO-IBD associated with skin inflammation and susceptibility to gastrointestinal and skin infections ( 209 ). ADAM17 has been shown to cleave the pro-inflammatory cytokine TNF-α, which is produced as membrane-bound precursor after activation ( 210 212 ). In line, PBMCs from patients with ADAM17 deficiency produce reduced amounts of TNF-α upon LPS stimulation ( 209 ).…”
Section: Inflammasome Dysregulation In Monogenic Veo-ibdmentioning
confidence: 99%
“…In line, PBMCs from patients with ADAM17 deficiency produce reduced amounts of TNF-α upon LPS stimulation ( 209 ). TNF-α-mediated activation of NF-κB signaling has been shown to induce expression of NLRP3 inflammasome components (e.g., NLRP3, IL-1β, and IL-18) and modulate pyrin inflammasome activity ( 210 , 213 , 214 ). In line, targeting TNF-α in a mouse model of autoinflammation caused by NLRP3 mutations was shown to ameliorate symptoms ( 213 ).…”
Section: Inflammasome Dysregulation In Monogenic Veo-ibdmentioning
confidence: 99%
“…Amphiregulin (AREG) is a ligand of epidermal growth factor receptor (EGFR), which is widely expressed in cardiomyocytes and fibroblasts [ 8 ]. Under physiological conditions, the activation of EGFR in the heart induces major intracellular signal cascades and control fibroblast proliferation, migration and collagen synthesis.…”
Section: Introductionmentioning
confidence: 99%